(untitled) (Scientific journal of the Fergana State University, 2025)
Current global processes are prompting the convergence of nation-states and their integration in economic, political, social, ideological, and cultural aspects. These trends manifest, to some extent, as a form of cosmopolitanism, becoming more pronounced under the influence of globalization processes. This article analyzes modern definitions of the concept of "cosmopolitanism" and outlines the main directions of this phenomenon.